Step * 1 1 of Lemma bag-remove1-member

.....subterm..... T:t
1:n
1. Type
2. eq EqDecider(T)
3. T
4. bs Base
5. b1 Base
6. bs b1 ∈ pertype(λas,bs. ((as ∈ List) ∧ (bs ∈ List) ∧ permutation(T;as;bs)))
7. bs ∈ List
8. b1 ∈ List
9. permutation(T;bs;b1)
10. as bag(T)
11. ({x} bs) ({x} as) ∈ bag(T)
12. bag-remove1(eq;{x} bs;x) (inl as) ∈ (bag(T)?)
⊢ as b1 ∈ bag(T)
BY
(FLemma `bag-append-cancel` [-2] THEN Auto) }


Latex:


Latex:
.....subterm.....  T:t
1:n
1.  T  :  Type
2.  eq  :  EqDecider(T)
3.  x  :  T
4.  bs  :  Base
5.  b1  :  Base
6.  bs  =  b1
7.  bs  \mmember{}  T  List
8.  b1  \mmember{}  T  List
9.  permutation(T;bs;b1)
10.  as  :  bag(T)
11.  (\{x\}  +  bs)  =  (\{x\}  +  as)
12.  bag-remove1(eq;\{x\}  +  bs;x)  =  (inl  as)
\mvdash{}  as  =  b1


By


Latex:
(FLemma  `bag-append-cancel`  [-2]  THEN  Auto)




Home Index